2015
DOI: 10.1590/1516-635x1704459-466
|View full text |Cite
|
Sign up to set email alerts
|

Beauveria Bassiana Applied to Broiler Chicken Houses as Biocontrol of Alphitobius Diaperinus Panzer (Coleoptera: Tenebrionidae), an Avian Pathogens Vector

Abstract: Beauveria bassiana is naturally found in broiler chicken houses, and has been shown to be active against the lesser mealworm, Alphitobius diaperinus. The effectiveness of soil application of B. bassiana in emulsifiable oil-type formulation (Unioeste 4 isolate) to control the lesser mealworm in commercial poultry house was evaluated. The fungus was applied to the dirt floor of poultry house at 4.2 × 10 9 conidia/m 2 (treated aviary) and the insect population was assessed before and 96, 146 and 216 days after ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Additionally, the emergence of resistant insect populations can occur (GARG et al, 2004;UEMURA et al, 2008;CHERNAKI et al, 2011). Studies with entomopathogenic fungi (ROHDE et al, 2006;ALVES et al, 2015), insecticidal plants (MARCOMINI et al, 2009;ALVES et al, 2012) and inert powders (SANTORO et al, 2010;ALVES et al, 2012) have shown them to be potential alternatives for insect control. Among the latter, highlight is given to diatomaceous earth (DE).…”
Section: Abstract: Diatomaceous Earth (De) Is An Inert Powdermentioning
confidence: 99%
“…Additionally, the emergence of resistant insect populations can occur (GARG et al, 2004;UEMURA et al, 2008;CHERNAKI et al, 2011). Studies with entomopathogenic fungi (ROHDE et al, 2006;ALVES et al, 2015), insecticidal plants (MARCOMINI et al, 2009;ALVES et al, 2012) and inert powders (SANTORO et al, 2010;ALVES et al, 2012) have shown them to be potential alternatives for insect control. Among the latter, highlight is given to diatomaceous earth (DE).…”
Section: Abstract: Diatomaceous Earth (De) Is An Inert Powdermentioning
confidence: 99%
“…However, fungi could be applied either as a powder or as a fat formulation in pheromone traps, with the pathogen being protected from the litter fungicide, and the insects being brought into contact with the pathogen in the pheromone traps. [46][47][48][49][50] In conclusion, our results suggest that alarm and aggregation pheromones can be deployed under poultry house conditions to trap significant numbers of adult A. diaperinus. Further long-term studies are underway to determine whether pheromone deployment can be combined with suitable entomopathogenic fungi to maintain A. diaperinus populations at low levels over time, and to evaluate the potential for using these components as part of an integrated A. diaperinus management strategy.…”
Section: Discussionmentioning
confidence: 61%
“…We believe that this combined approach has the potential to be used for A. diaperinus management. However, fungi could be applied either as a powder or as a fat formulation in pheromone traps, with the pathogen being protected from the litter fungicide, and the insects being brought into contact with the pathogen in the pheromone traps …”
Section: Discussionmentioning
confidence: 99%
“…Studies have already been performed in primary animal and plant production, food industry and even in hospitals (Zhao et al, 2006;Vandini et al, 2014;Luyckx et al, 2016;Bosmans et al, 2017;Hossain et al, 2017;Zheng et al, 2018). However, the possibility to use biocontrol agents against persistent pathogenic strains in the broiler environment has received only limited attention (Alves et al, 2015). In this research, a realistic in vitro model for bio lm formation on the inside of the DWS was developed and validated.…”
Section: Discussionmentioning
confidence: 99%